2008
DOI: 10.2174/1874210600802010078
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Reductase 3 (CBR3) Mediates 9-cis-Retinoic Acid-Induced Cytostatis and is a Potential Prognostic Marker for Oral Malignancy

Abstract: The molecular mechanisms of growth suppression by retinoic acid (RA) were examined. Our results suggest that the cytostatic effects of RA could be mediated by the activation of endogenous CBR3 gene in oral squamous cell carcinomas (OSCCs), and the expression is a potential marker for oral malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Cbr3 (carbonyl reductase 3) catalyzes the reduction of many endogenous and xenobiotic carbonyl compounds, including steroids and prostaglandins, to their corresponding alcohols. Its expression is reduced in oral squamous cell carcinoma cells when compared to premalignant dysplasias and hyperplasias and has been associated with reduced cell growth and motility (43). Histidine decarboxylase (Hdc) is a member of the histidine metabolism pathway and is responsible for the biosynthesis of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Cbr3 (carbonyl reductase 3) catalyzes the reduction of many endogenous and xenobiotic carbonyl compounds, including steroids and prostaglandins, to their corresponding alcohols. Its expression is reduced in oral squamous cell carcinoma cells when compared to premalignant dysplasias and hyperplasias and has been associated with reduced cell growth and motility (43). Histidine decarboxylase (Hdc) is a member of the histidine metabolism pathway and is responsible for the biosynthesis of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the link between CBR3 and apoptosis is supported by study of Ohkura-Hada et al who showed that CBR3 mediates, at least in part, the cytostatic effects of 9-cis-retinoic acid (RA) in oral squamosus cell carcinoma (OSCC) cells [26]. The anticancer activities of RAs are attributable to growth suppression, the induction of apoptosis, and the suppression of cell migration.…”
Section: Association With Cancermentioning
confidence: 97%
“…There are several retinod analogues that are widely used for therapeutic purposes [152]. Ohkura-Hada et al demonstrated that 9-cis-RA induced CBR3 expression in the OSCC cell line, Ca9-22 [26]. Further, the transfection of Ca9-22 cells with the CBR3 expression vector caused reduced cell growth and migration potential, suggesting that CBR3 is a mediator of cytostatic effects by RA.…”
Section: Association With Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…CBR3 is involved not only in the metabolism of anthracyclines, but also in some physiological regulations. Treatment with 9‐ cis ‐retinoic acid induces CBR3 gene expression, and the induced enzyme suppresses cell growth and migration potential in oral squamous cell carcinomas (Ohkura‐Hada et al, ). Furthermore, increased expression of the CBR3 gene in human adipose tissues is negatively associated with fasting insulin and systemic insulin resistance, suggesting that CBR3 modulates the diabetic state (Chang et al, ).…”
Section: Introductionmentioning
confidence: 99%